Predation by invasive signal crayfish on early life stages of European barbel may be limited. Issue 5 (7th April 2017) - Copp, Gordon H.; Godard, Michael J.; Vilizzi, Lorenzo; Ellis, Adam; Riley, William D.
Abstract: To determine whether or not signal crayfish Pacifastacus leniusculus and native white‐clawed crayfish Austropotamobius pallipes prey on European barbel Barbus barbus eggs, interstitial free‐embryos and emergent larvae, experiments were undertaken in salmonid (substratum) incubators (six treatments, four controls) fitted with video recorders. No corpses or remains of emergent barbel larvae or eggs, or parts thereof, were observed in any of the incubators containing buried eggs, and no emergent larvae showed any sign of attack. However, video evidence of a signal crayfish catching and consuming a barbel larva was obtained. There were no statistically significant differences between white‐clawed and signal crayfish either in carapace length or weight at the beginning and end of the experiments. The conservation implications of these results are discussed.